STORYTELLING SEBAGAI UPAYA MENINGKATKAN KONSUMSI SAYUR - Nor Z. Asy’ariyah; Yuni S. Arief; Ilya Krisnana (Pediomaternal Nursing Journal, 2014)
Introduction: Preschool vegetable consumption still less than recommendation that lack of knowledge and attitude of ignoring the importance of eating vegetables is being the reasons. Storytelling is a method that suitable for cognitive and affective development of preschool which able to imagine new perspectives and invite learning experiences from the characters. The purpose of this study was to examine the effects of storytelling on knowledge and attitude vegetable consumption for preschool at Nitasari Kindergarten Mojo Gubeng Surabaya.Method: A Quasy Experiment method with pretest-posttest control group design was used. The populations were students of Nitasari Kindergarten Surabaya in the B class which has 37 students. Samples were taken by purposive sampling technique. The independent variable is storytelling with flash card as a media, while the dependent variable is the knowledge and attitude of preschool in vegetable consumption. Data were collected by using questionnaire and interview then analyzed using level of significance p<0.05 by Wilcoxon Sign Rank Test and Mann Whitney U test.Results: Result showed that there was difference in vegetable consumption knowledge level between treatment and control groups with p=0.000; and there was difference in vegetable consumption attitude between treatment and control groups with p=0.003.Conclusion: It can be concluded that storytelling has effect on knowledge and attitude vegetable consumption for preschool. Storytelling should carry out by competence storyteller and for further studies should examine into action domain.